Insights into the Titania (TiO2) Photocatalysis on the Removal of Phthalic Acid Esters (PAEs) in Water - Norfarahim Mohd Tubillah; Sheela Chandren (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
In this era of globalization, plastic is regarded as one of the most versatile innovations, finding its uses ranging from packaging, automotive, agriculture, and construction to the medical and pharmaceutical industries. Unfortunately, the single-use nature of plastics leads to ecological and environmental problems. Among conventional disposal management of plastic waste are landfilling dumping, incineration, and recycling. However, not all plastic waste goes into disposal management and ends up accumulating in lakes, rivers, and seas. In the aquatic environment, the action of photochemical weathering plastics has resulted in the release of chemical additives such as phthalic acid esters (PAEs), an important plasticizer added to plastic products to improve their softness, flexibility, and durability. Nowadays, PAEs have been ubiquitously detected in our environment and numerous organisms are exposed to PAEs to some extent. As PAEs carry endocrine disruptive and carcinogenicity properties, an urgent search for the development of an efficient and effective method to remove PAEs from the environment is needed. As a viable option, titania (TiO2) photocatalysis is a promising tool to combat the PAEs contamination in our environment owing to its high photocatalytic activity, cost-effectiveness, and its ability to totally mineralize PAEs into carbon dioxide and water. Hence, this paper aims to highlight the concerning issue of the contamination of PAEs in our aquatic environments and the summary of the removal of PAEs by TiO2 photocatalysis. This review concerning the significance of knowledge on environmental PAEs would hopefully spark huge interest and future development to tackle this plastic-associated pollutant. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).